The use of digitally interpreted satellite imagery, with special reference to topographical shadow effects, as an aid to vegetation mapping in the Hottentots Holland Mountain catchment area of the Western Cape Province - Newby, Terence Styan (Department of Environmental and Geographical Science, 2015)
This report includes a summary account of the operation of the LANDSAT 2 satellite and describes some of the procedures for extracting information, relating to vegetation, from digital imagery. The effect of topographic shadow on the imagery is explained and a short discussion of mountain fynbos, the natural vegetation of the mountains of the Western Cape Province of South Africa, is included. The report explains the methods used to estimate the amount of shadow on the imagery of the study area and to investigate the potential of various spectral band ratios for giving useful management information. It was found that approximately seventeen percent of the image of the Hottentots Holland Mountain Catchment Area is affected by topographic shadow. No meaningful information could be extracted from the shadowed areas, by digital image processing. Band ratioing did however, result in strong correlations between spectral values and vegetation height, percentage cover and biomass, as well as leaf surface area, veld condition and aspect, for sun illuminated areas.